Clinical Predictors of Aspirin Resistance in Patients with Type 2 Diabetes: A Systematic Review and Meta-Analysis - Fan Zhang; Hongyan Zheng (Reviews in Cardiovascular Medicine)
Background: Aspirin treatment is recommended as a secondary prevention strategy and could be a potential primary prevention strategy for cardiovascular disease (CVD) in patients with type 2 diabetes mellitus (T2DM). However, aspirin resistance is notably common among diabetic patients, compromising the efficacy of aspirin treatment. Hence, our study sought to assess the clinical predictors of aspirin resistance (AR) in T2DM patients. Methods: We conducted a systematic search of three major medical databases (PubMed, Embase, and Cochrane Library) to identify relevant articles up to September 17, 2024. Details of publications and investigated parameters were extracted from the selected studies. The meta package in the R language software was utilized to synthesize the evidence concerning clinical predictors of AR. We applied either a fixed- or random effects model based on the heterogeneity observed among the included studies. The pooled results were visually displayed using forest plots. Results: In total, 10 publications were finally included in our study (n = 2113 patients). AR was predominantly linked to specific laboratory parameters, particularly those indicative of heightened insulin resistance and inadequate lipid management. Specifically, the laboratory parameters associated with AR included fasting glucose level (mean difference (MD) = 8.21; 95% confidence interval (CI) = 2.55 to 13.88), glycated hemoglobin (MD = 0.22; 95% CI = 0.06 to 0.38), high-density lipoprotein (HDL) level (MD = –2.02; 95% CI = –3.62 to –0.42), low-density lipoprotein (LDL) level (MD = 7.00; 95% CI = 2.87 to 11.13), total cholesterol level (MD = 9.52; 95% CI = 4.37 to 14.67), and triglyceride levels (MD = 12.51; 95% CI = 3.47 to 21.55). Conclusions: Markers associated with dyslipidemia and blood glucose levels are robust indicators of AR in individuals with T2DM. These findings imply that assessing lipid and glucose regulation could enhance the development of personalized preventive approaches for vascular complications linked to diabetes. The PROSPERO registration: CRD42023388170, https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=388170